A Look at the impacts of the application of collaborative technologies in foreign language teaching; Insights from lecturers - khasawneh, Mohmmad (Research Journal in Advanced Humanities, 2024)
Collaborative technological tools are affirmed to be effective in language education. This study discusses how collaborative technological tools have enhanced the teaching and learning of foreign languages (FLs). The study adopts a quantitative method and surveyed 291 FL lecturers drawn across different universities. A digitally designed Google questionnaire Form was used in the survey, and analysis was conducted using relevant statistical measures. The analysis focuses on Zoom, Microsoft Teams, Google Meet, and TeamViewer. It is worth noting that Zoom and Google Meet indicate very high levels of perceived ease of use, with scores of 89.06% and 90.13%, respectively. Microsoft Teams and TeamViewer, while acknowledged for their user-friendly nature with percentages of 57.97% and 77.95%, respectively, have somewhat lower percentages in comparison. The results demonstrate a strong consensus among university lecturers about the perceived use and efficacy of collaborative technology tools in teaching foreign languages. According to the survey’s findings, all the survey questions were entirely accepted, ranging from 89.60% to 96.14%. The scope of mean values ranging from 4.86 to 5.39 adds another aspect, indicating the highest acceptance level. These scores show the shared understanding that incorporating collaborative technologies significantly enlarges the teachers’ effectiveness, improves communication efficiency, promotes language proficiency development, and facilitates the creation of engaging learning experiences in foreign language teaching. Because of the accompanying optimism and enthusiasm, many language educators view communicative technologies as indispensable resources for modern language instruction. Overall, the results support that a usability factor should be considered when choosing collaborative technologies for teaching FL, where the user and their needs are central, and the idea of constructivism plays a significant role.